Individual experience as a key to success for the cuckoo catfish brood parasitism - Zimmermann, Holger; Blažek, Radim; Polačik, Matej; Reichard, Martin (Nature communications, 2022)
Brood parasites are involved in coevolutionary arms races with their hosts, whereby adaptations of one partner elicit the rapid evolution of counter-adaptations in the other partner. Hosts can also mitigate fitness costs of brood parasitism by learning from individual or social experience. In brood parasites, however, the role of learning can be obscured by their stealthy behaviour. Cuckoo catfish (Synodontis multipunctatus) parasitise clutches of mouthbrooding cichlids in Lake Tanganyika and are the only non-avian obligate brood parasites among vertebrates. We experimentally demonstrate that cuckoo catfish greatly enhance their efficiency in parasitising their hosts as they learn to overcome host defences. With increasing experience, cuckoo catfish increased their parasitism success by greater efficiency through improved timing and coordination of intrusions of host spawnings. Hence, within the coevolutionary arms races, brood parasites learn to overcome host defences during their lifetime.
Keywords: Symbiosis; fyziologická adaptace; Catfishes; Animals; Cichlids; ptáci; sumci; Birds; symbióza; zvířata; cichlidy; Adaptation, Physiological